2007
DOI: 10.1097/jom.0b013e31803b94f9
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Detecting the Mold Syncephalastrum in Clinical Specimens of New Orleans Residents After Hurricanes Katrina and Rita

Abstract: After the extensive flooding in New Orleans following Hurricanes Katrina and Rita, thousands of homes in the flooded areas had significant growth of mold. The potential health effects from exposures to these extraordinary environments are unknown. In February 2006, we investigated a cluster of patients with clinical specimens yielding Syncephalastrum, a zygomycete that rarely causes infection. We identified the cases of eight patients from September 12, 2005, to January 12, 2006, with specimens from sputum, br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 15 publications
0
25
0
Order By: Relevance
“…Syncephalastrum spp. were the only thermotolerant Mucormycetes detected in 47% of indoor air samples from heavily damaged houses and in none of the mildly damaged houses in the flooded areas of New Orleans after Hurricanes Katrina and Rita (272,273). Workers in farm operations, particularly those who handle, harvest, and process food and feed after harvest, may be particularly predisposed to exposure to airborne S. racemosum (2).…”
Section: Syncephalastrum Racemosummentioning
confidence: 99%
See 3 more Smart Citations
“…Syncephalastrum spp. were the only thermotolerant Mucormycetes detected in 47% of indoor air samples from heavily damaged houses and in none of the mildly damaged houses in the flooded areas of New Orleans after Hurricanes Katrina and Rita (272,273). Workers in farm operations, particularly those who handle, harvest, and process food and feed after harvest, may be particularly predisposed to exposure to airborne S. racemosum (2).…”
Section: Syncephalastrum Racemosummentioning
confidence: 99%
“…The ability of Syncephalastrum species to cause ear infections and mycotic keratitis and isolation of these organisms in wound culture are not clear, as reports have not provided details about such cases (238,324,345). Also, researchers identified a cluster of eight patients with clinical specimens yielding Syncephalastrum isolates after natural disasters (272). All of these patients appeared to have transient colonization of Syncephalastrum spp.…”
Section: Syncephalastrum Racemosummentioning
confidence: 99%
See 2 more Smart Citations
“…A case series by Rao et al showed an increase in the isolation of Syncephalastrum spp. in clinical specimens of New Orleans residents in one area hospital following the hurricanes (40). All eight of the clinical specimens were believed to be colonization and not true infection because all patients improved with treatment for other illnesses and without appropriate treatment for Syncephalastrum.…”
Section: Clinical Illness Seen Following Katrina and Ritamentioning
confidence: 99%